Spatio-temporal pattern of cross-continental invasion: Evidence of climatic niche shift and predicted range expansion provide management insights for smooth cordgrass. (July 2022) - Banerjee, Achyut Kumar; Liang, Xinru; Harms, Nathan E.; Tan, Fengxiao; Lin, Yuting; Feng, Hui; Wang, Jiakai; Li, Qingwei; Jia, Youxin; Lu, Xinyu; Liu, Yangbeijia; Cao, Renqi; et al.
Graphical abstract: Highlights: Aimed to identify global susceptible regions to smooth cordgrass invasion. Characterized climatic niche dynamics at spatial and temporal scales. Observed significant climatic niche expansion with a short lag period. Future range expansion predicted with marginal climate change. Mangroves and protected areas are at risk to ongoing and future invasions. Abstract: Introduction and spread of the halophyte Spartina alterniflora is one of the largest continental-scale biological invasion events in Asia and the Americas. Rapid globalization and broad environmental tolerance of the species increase the chance of novel invasions. Thus, we aimed to identify susceptible regions to inform prevention and control activities. A comprehensive global occurrence dataset and corresponding bioclimatic variables were used to characterize the species' climatic niche and predict current and future potential distributions. Conservatism of climatic niche between native and non-native ranges was tested, and climatic niche dynamics were analysed at spatial and temporal scales. The ensemble of eight species distribution models and eight climate change models was used to map the potential distribution of S. alterniflora under current and future climate conditions. We investigated the susceptibility of threatened ecosystems like mangroves and protected areas to S. alterniflora invasion to better inform management decisions. Our study revealed wide climatic tolerance and significant niche expansion of the species from humid regions of its native range to dry and arid environments of its non-native range with a very short lag period. With a marginal increase in temperature and precipitation in the future, range expansion was predicted towards higher latitude and more inland areas. The mangroves area, salt marshes, and protected areas that are at risk of ongoing and future invasions were identified. Given the invasion potential of S. alterniflora, the areas identified as climatically susceptible for the species' establishment, both in current and future climates, should be prioritized for management actions.